A High Rigidity and Precision Scanning Tunneling Microscope with Decoupled XY and Z Scans. (14th November 2017) - Chen, Xu; Guo, Tengfei; Hou, Yubin; Zhang, Jing; Meng, Wenjie; Lu, Qingyou
Abstract : A new scan-head structure for the scanning tunneling microscope (STM) is proposed, featuring high scan precision and rigidity. The core structure consists of a piezoelectric tube scanner of quadrant type (forX Y scans) coaxially housed in a piezoelectric tube with single inner and outer electrodes (forZ scan). They are fixed at one end (called common end). A hollow tantalum shaft is coaxially housed in theX Y -scan tube and they are mutually fixed at both ends. When theX Y scanner scans, its free end will bring the shaft to scan and the tip which is coaxially inserted in the shaft at the common end will scan a smaller area if the tip protrudes short enough from the common end. The decoupledX Y andZ scans are desired for less image distortion and the mechanically reduced scan range has the superiority of reducing the impact of the background electronic noise on the scanner and enhancing the tip positioning precision. High quality atomic resolution images are also shown.